Synthesis and Characterization of Mesoporous Silica Modified with Purpald and Its Application in the Preconcentration of Cu2+ and Cd2+ from Aqueous Samples through Solid-Phase Extraction - Wondracek, Marcos Henrique Pereira; Jorgetto, Alexandre de Oliveira [UNESP]; da Silva, Adrielli Cristina Peres [UNESP]; Schneider, José Fabián; Pedrosa, Valber de Albuquerque [UNESP]; Saeki, Margarida Juri [UNESP]; de Castro, Gustavo Rocha [UNESP] (MDPI, 2023)
The synthesis of an organofunctionalized mesoporous silica was accomplished by a two-step process involving (1) the co-condensation of a silylant agent at the surface of silica, followed by (2) the immobilization of Purpald (ligand) at the organic termination of the silytant agent. The characterization of the organofunctionalized material indicated the presence of NH2 groups, and the immobilization of the ligand was confirmed by 29Si- and 13C-nuclear magnetic resonance. The material’s surface area was determined as 370 m2 g−1. Batch adsorption experiments enabled the determination of optimum pH conditions for the adsorption of Cu(II) and Cd(II). Under optimal pH, the pseudo-second-order kinetic model and Langmuir model provided the best correlations to describe the materials adsorption behavior, suggesting a chemisorption mechanism. When tested in continuous-flow preconcentration experiments, the flow rate and eluent concentration demonstrated to affect the removal of Cu(II) and Cd(II), while the buffer concentration had an effect only over the adsorption of Cu(II). Under optimized preconcentration conditions, it was possible both to determine the concentrations of Cu(II) and Cd(II) in samples such as mineral water, ground water, tap water and river water. Ions commonly found in drinking and natural waters (Na+, K+, Ca2+, Mg2+, Fe3+, Ba2+, Cl−, SO42−, HCO3−, and H2PO4−) did not affect the preconcentration of any of the studied analytes. Reutilization experiments indicated that the adsorbent material can withstand at least 40 adsorption/desorption preconcentration cycles with no efficiency loss.
Keywords: adsorption; preconcentration; solid-phase extraction; toxic metals